(3cJGH aj GdCOhjIs
(3ChdgG (B:s
(3Ef Chd eG GaJJM GdNWGH GdJYXje HPcQ Gddg hdeG cGfJ GdCOhjI hGdCZPjI eGOI JMaX UMI GdEfSGf deOGhGI GSbGe GdCHOGf cGf ef GdhGLH Ydi GdWHjH eYQaI eGgjJgG s
(3BNQgG (B:s
(3ZdTGf (B: (3gh GdLOhGQ , cd eeG aSQ Hg PcQ ai MQag Je GdcJGH s
(3HfGg Ydi LOGhd QJH GdCOhjI ajgG Ydi GdCHLOjIs
(3YdjgG JUMjMs
(3hai UOQgG JGQjN (B1255s
(3HYVg HGdMeQI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdWHs